TRANSFORMASI STRATEGI PROMOSI DIGITAL UMKM MELALUI PELATIHAN FOTO PRODUK BERBASIS PRAKTIK MEDIA SOSIAL - Muafi, Siti Liza; Asmiarti, Yufrida; Kusumaningtyas, Nadya; Rohman, Farkhan Nur; Franscikal, Aditya; Pamungkas, Yoma Bagus (Intimas, 2026)
Abstract The development of social media has made visual content a crucial element in MSME promotional strategies. However, many MSME actors still face limitations in producing attractive product photographs that align with the characteristics of social media platforms. This Community Service Program (PKM) aimed to enhance the understanding and skills of MSME actors in Jomblang Subdistrict in product photography to support the optimization of digital promotion. The implementation method employed a participatory and applicative approach through stages of needs analysis, theoretical training, hands-on product photography practice using simple equipment, as well as evaluation and mentoring. Evaluation was conducted using pretests and posttests to measure improvements in participants’ understanding. The results showed a significant increase in the average score from 52.4 in the pretest to 82.6 in the posttest. In addition, the quality of participants’ product photographs improved in terms of lighting, composition, and background selection, which contributed to increased promotional interaction on social media. These findings demonstrate that practice-based product photography training is effective, easy to adopt by MSMEs, and contributes to enhancing the sustainability of digital promotional competitiveness.